Benefits and challenges of teaching English in Brazilian regular schools - Fragozo, Carina Silva (BELT - Brazilian English Language Teaching Journal, 2011)
Although the present society requires the knowledge of foreign languages, English teaching and learning are usually considered unsatisfactory in Brazilian regular schools. This article comments on the benefits of teaching English in regular schools, an aspect that sometimes is forgotten in researches that discuss language teaching in Brazilian Basic Education. It also presents some of challenges to be faced by teachers in this context, together with some ideas for dealing with them.